Key players in the regulation of iron homeostasis at the host-pathogen interface - Ullah, Inam; Lang, Minglin (Frontiers in Immunology, 2023)
Iron plays crucial role in the biochemistry and development of nearly all living organisms. Iron starvation of pathogens during infection is a striking feature of the host to get rid of infection. In mammals and some animals, iron is essentially obtained from diet and recycled from erythrocytes.Free iron is cytotoxic and is readily available to invading pathogens. During infection, most pathogens utilize host iron for their survival. Therefore, to ensure limited free iron, host natural system denies this metal in a process termed nutritional immunity. In this fierce battle for iron, host wins over some pathogens, but others have evolved mechanisms to overdrive the host barriers.Production of siderophores, heme iron thievery and direct binding of transferrin and lactoferrin to bacterial receptors are some of the pathogens success strategies that are also highlighted in the review. The intricate interplay between hosts and pathogens in iron alteration systems is crucial for understanding host defense mechanisms and pathogen virulence. This review aims to elucidate the current understanding of host and pathogen iron alteration systems and propose future research directions to enhance our knowledge in this field.